Proposal of an Equal-Stiffness and Equal-Stroke 2D Micro-Positioning Platform Driven by Piezoelectric Actuators - Feng Sun; Yansong Hao; Fangchao Xu; Junjie Jin; Qiang Li; Ling Tong; Ming Zhang; Xiaoyou Zhang (Actuators, 2020)
Micro-positioning platform plays an important role in the field of precision positioning such as microelectronics, robotics and biomedicine. This paper proposes an equal-stiffness and equal-stroke 2D micro-positioning platform, which is driven by piezoelectric actuators. The overall structure of the 2D micro-positioning platform adopts a nested structure and the displacement magnification mechanism adopts two hourglass displacement magnification mechanisms. The displacement magnification ratio of the hourglass displacement magnification mechanism was studied, and its structural parameters were optimized. Static stiffness analysis and simulation analysis of the micro-positioning platform were carried out. The simulation stiffness of the micro-positioning platform in the XY direction is 46873 N/m and 46832 N/m respectively. The experimental prototype of the micro-positioning platform was built. Through the measurement experiment with the prototype, the maximum stroke of the micro-positioning platform in the XY direction is 489 μm and 493 μm respectively; the maximum coupling ratio in the XY direction is 2.38% and 2.70% respectively. The research indicates that the micro-positioning platform had the characteristics of small size, equal long stroke, equal stiffness and low coupling ratio in the XY direction.